ORIENTASI POLITIK PELAJAR SMA DI KOTA SEMARANG - savira anindita; Susilo Utomo; Sulistyowati . (Journal of Politic and Government Studies, 2017)
Political socialization is a process of inculcating political orientation throughpolitical socialization agents to an individual. In the present study, these socializationagencies are independent variables (X) namely, Family (X1), School (X2) and SocialMedia (X3) which have relationship to the political orientation which is thedependent variable (Y).The purpose of this study is to know how the influence of Family, School andSocial Media on the formation of political orientation of high school students in thecity of Semarang. This research uses quantitative approach with explanatoryresearch type. The sampling procedure uses probability sampling. Data wereobtained through questionnaires containing 25 questions distributed to respondentswhere the population is high school students in Semarang, with N = 191 students.The scale used is the ordinal scale. Furthermore, in the data analysis performed withcomputer program SPSS 16.0.The results of this study are Family, School and Social Media have aninfluence on the formation of political orientation high school students in the city ofSemarang. Family (X1) with political orientation (Y) has a strong enoughrelationship with correlation coefficient 0.490; School (X2) with political orientation(Y) has a strong enough relationship with correlation coefficient 0.594; Social media(X3) with political orientation (Y) has a strong enough relationship with correlationcoefficient 0.467; And families, schools, and social media together have a significantinfluence on the formation of political orientation.Keywords: Political socialization agent, Political orientation